Unifloral ajwain honey ameliorates differential inhibition of matrix metalloproteinases 2 and 9 protein, cytotoxicity, and antioxidant potential - Shruti S. Kulkarni (Elsevier, 2021)
Background: Free radicals lead to inflammation, which in turn could intervene several chronic diseases including cancer. The promising scientific finding for anti-cancer properties of honey is an area of great interest. Objective: The present study was designed to investigate the in vitro biological effects (cytotoxic, and anti-inflammatory through differential inhibition of metalloproteinases and antioxidant) of unifloral Ajwain honey along with its physicochemical properties (pH, moisture, ash content, electrical conductivity, color, protein). Materials and methods: Three Ajwain honey samples (AJ-1, AJ-2, and AJ-3) were collected from different geographical origins of Western Ghats of India. Melissopalynological analysis was carried out to confirm uniflorality. Physicochemical analysis for ash, moisture content, pH, electrical conductivity, color, and total protein was estimated. Total polyphenol, total flavonoid content, and ferric reducing ability of plasma assay were determined using appropriate methods. The cytotoxic effect was assessed against breast cancer cells (MDA-MB-231) by 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and the anti-inflammatory activity was evaluated by gelatin zymography of matrix metalloproteinases MMP-2 and MMP-9 proteins. Results: Melissopalynological analysis confirmed pollens from Ajwain plant's and so-called Ajwain honey. MTT assay depicted inhibitory trend for all honey samples across the concentrations (6.25–100 mg/ml) as compared to untreated cells. Gelatin zymography of metalloproteinases (MMP-2 and MMP-9) showed inhibitory tendency in all Ajwain honey samples. The AJ-3 honey sample had the highest inhibition at 0.625%. A significant correlation between honey color, pH, and protein content was perceived throughout the study. Conclusion: This study highlights the in vitro biological evidence for possible therapeutic application of Ajwain honey samples in cytotoxic, anti-inflammatory, and antioxidant management as well as can be considered a potent source of supplements in human nutrition.